Smart modular lighting control system with dual-beam luminaires. (June 2015) - Caicedo, D; Pandharipande, A; Vissenberg, MCJM
We consider a smart lighting system with multiple dual-beam luminaires, with co-located occupancy and light sensors. A dual-beam luminaire emits a hollow beam and a narrow beam, suitable, respectively, for providing ambient and task lighting both controllable independently. We consider an occupancy- and daylight-adaptive lighting system, wherein the luminaire controller determines the dimming levels of the dual beams such that the lighting system provides a desired illuminance based on local occupancy and light sensor inputs. We present a method for calibrating the light sensors to obtain control set-points and a controller design so that the set-points may be attained. The proposed system performance is compared with a standard-beam lighting system using lighting simulations. We find that the dual-beam lighting system provides higher illumination and power saving in comparison to the standard-beam lighting system, given the additional degree of freedom provided by the two optical beams.